Hyperprolactinaemia in patients with heart failure: clinical and immunogenetic correlations - LIMAS, CJ; Kroupis, C.; Haidaroglou, A; Cokkinos, D.V. (Eur.J.Clin.Invest, 2002)
BACKGROUND: Prolactin represents a stimulatory link between the neuroendocrine and immune systems, but its involvement in the neurohumoral adaptations to heart failure (HF) has not been explored. METHODS: We prospectively studied 55 patients (45 males, 10 females, age 48 +/- 7 years) with NYHA Class II/III HF due either to dilated cardiomyopathy (CMP) (n = 33) or ischemic heart disease (IHD) (n = 22). Serum prolactin levels were determined by radioimmunoassay, soluble interleukin-2 receptor (sIL-2R) levels by enzyme-linked immunoassay and HLA-DQ genotyping with PCR. Left ventricular ejection fraction (LVEF) and end-diastolic diameter (LVEDd) were assessed echocardiographically. RESULTS: Hyperprolactinaemia (17.3 +/- 4 ng mL-1 [Group I] vs. 4.64 +/- 2 ng mL-1 [Group II], P < 0.01) was found in 14 patients (8 with IHD, 6 with CMP). The distribution of HLA-DQB1 alleles was compared in the two groups and showed a significant increase in the frequency of *0301 (86% in Group I vs. 45% in Group II, P < 0.05). Histidine at position 30 of the HLA-DQB1 gene was found in 22% of Group II but in none of Group I patients. Furthermore, there was an inverse correlation between the presence of histidine at position 30 and the levels of serum prolactin. Both sIL-2R levels, a marker of T-cell activation, and concanavalin A-stimulated lymphocyte proliferation were lower in Group I patients (561 +/- 106 vs. 804 +/- 109 pg mL-1 and 20.8 +/- 4 vs. 37.3 +/- 5 cpmX103 [3H] thymidine, respectively). LVEF was significantly higher (32 +/- 5%) and LVEDd smaller (62.0 +/- 6 mm) in Group I compared to Group II (25 +/- 4% and 68.0 +/- 5 mm, respectively, P < 0.01) patients. CONCLUSION: Hyperprolactinaemia presents in 25% of patients with HF and may reflect decreased activation of T-lymphocytes associated with relatively preserved LV systolic function which is under immune-genetic control at the HLA-DQ locus
DA - 20020315 IS - 0014-2972 (Print) IS - 0014-2972 (Linking) LA - eng PT - Journal Article RN - 0 (HLA-DQ Antigens) RN - 0 (HLA-DQ beta-Chains) RN - 0 (HLA-DQB1 antigen) RN - 0 (Receptors, Interleukin-2) SB - IM
Keywords: Adult; Alleles; Cardiomyopathy,Dilated; Complications; Female; genetics; Greece; Heart failure; HLA-DQ Antigens; HLA-DQ beta-Chains; Humans; Hyperprolactinemia; immunology; In Vitro Techniques; Lymphocyte Activation; Male; metabolism; Middle Aged; Myocardial Ischemia; Receptors,Interleukin-2; T-Lymphocytes